Do Vertical Contracts Lead to Foreclosure or to Efficiency Gains? An Empirical Study of the Food and Beverage Industry - Silvia Bertarelli (European Scientific Journal, ESJ, 2024)
This paper presents a research method to determine whether vertical contracts concluded between firms operating at different levels of the supply chain are efficient from the perspective of the most recent industrial organisation theory. In this view, some case studies are presented concerning antitrust investigations against some large companies operating in the food and beverage sector in Italy. Despite the controversy surrounding the effects of vertical agreements, as they may be pro- or anti-competitive, the paper shows that not only market concentration but also intra-sectoral asymmetries are crucial factors to be assessed in order to distinguish between foreclosing and efficiency-enhancing agreements.